City of the future Constance. "Future city". Quality instead of square meter. - Dübner, Sven; Esper, Lukas; Stroh, Felix (My University, 2018)
By 2050, more than 70 % of the world's population will live in cities. This usually goes hand in hand with the increasing use of space and the simultaneous growth of per-capita residential space. However, the growth of cities must not necessarily signify a problematic development. Therefore, the "future city" implies a change of perspectives, away from the problem of growth, towards the challenge of growing smart and sustainable, for which suitable solutions within the respective city must be found. This paper is based on the project "City of the Future Constance" (Zukunftsstadt Konstanz) which is supported by the German Ministry of Research and Education (BMBF) as part of the Flagship Initiative "City of the Future". Within the City of the Future initiative, local communities, busines, civil society representatives and the scientific community cooperate with each other in order to implement processes and recommendations for action for the cities of the future in Germany. As part of the three-phase tendering, the first phase focused on the question "How will we live and reside in the year 2030?". The foundations for the vision were laid during the workshops of the participatory symposium. Through the change of perspectives on fictitious persons from the year 2030 and with the help of prepared personal profiles, the - presumed - living and housing needs of different age groups and milieus were described very concretely. The concrete needs related to four fields of action "City.Living", "City.Mixed", "City.Mobile" and "City.Intelligent". Building on the vision developed jointly in the first phase, the focus in phase two is on reducing the per-capita residential space. This question will first scientifically elaborated and, finally, also structurally implemented in a model district in phase 3. The goal is to develop a superior planning toolkit, which provides orientation for the sustainable development of all areas of the action program with regard to housing, focusing in particular on the topic of space efficiency and the resulting topics in the planning focus. Within a multi-day workshop the planning toolkit is going to be used by stakeholders, citizenry and planners to work out a comprehensive concept of development for the model district.
Keywords: Mittelstadt; Universitätsstadt; Stadtentwicklungsplanung; Stadtentwicklungskonzept; Nachhaltige Entwicklung; Smart City; Raumbedarf; Flächenverbrauch; Flächeneinsparung; Wohnungsgröße; Planungswerkzeug